Biology of Diachasmimorpha longicaudata, A Parasitoid of Carambola Fruit Fly, (Diptera; Tephritidae) - A. G., Ibrahim; I. P., Palacio; I., Rohani (Universiti Putra Malaysia Press, 1994)
The life cycle study of Diachasmimorpha longicaudata, a larval parasitoid of Bactrocera (B) sp. near Bactrocera dorsalis A, was conducted in the laboratory (26°C± 1.5°). There were 4 larval stages based on the size of the mouthhook. The first larval moult occurred in the newly formed pupanum of the host. The entire developmental periods for males and females were 16.3 ± 0.8 day and 17.5 ± 0.8 days, respectively. The average reproductive capacity per female during the life-span was 92 ± 4.5 eggs.